Nested PCR analysis of Plasmodium parasites - Snounou, Georges; Balbir, Singh (Humana Press, Inc., Totowa, NJ, 2002)
In the natural and untreated intermediate hosts, Plasmodium infections are maintained for extended and often lifelong periods. Parasitemia generally reaches its highest level in the first peak after inoculation, and only rises thereafter during increasingly brief and interspersed episodes. As the host acquires tolerance to higher numbers of multiplying parasites, the severity and duration of the clinical episodes that coincide with the parasite peaks diminish.